EVALUATING THE ROLE OF VILLAGE-OWNED ENTERPRISE (BUMDES) IN CONTRIBUTING TO VILLAGE INDEPENDENT REVENUE (PADES): CASE STUDY OF BENTENG GAJAH VILLAGE - Vinoli, Siska; Wisesa, W. Victo Anggara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Village-Owned Enterprises (BUMDes) aim to support rural economic independence through Village Independent Revenue (PADes). However, in Benteng Gajah Village, Maros, BUMDes Bulu Saukang remains inactive and has failed to contribute any PADes. Despite local potential such as agriculture, tourism, and livestock, BUMDes faces challenges hindering its operational capacity and sustainability. This study aims to identify core barriers to BUMDes performance and propose solutions to strengthen its role in the village economy. A qualitative case study approach was used, with interviews with ten key village stakeholders, including BUMDes officers, government officers, and community members. Thematic analysis was conducted using NVivo 15, guided by Van Meter and Van Horn’s policy implementation model. Findings show that BUMDes performance is hindered by limited human capacity, weak strategic planning, legal ambiguity, and low public participation. Seven key challenges were identified, including operational discontinuity, lack of innovation, and over-dependence on key individuals. In response, the study proposes five strategies: institutional strengthening, business diversification, external collaboration, community empowerment, and branding. These recommendations aim to reposition BUMDes as a community-driven enterprise that can contribute to PADes and improve local welfare.